The Concept Of "Inoyat" (العناية (In The Philosophical Views Of Abu Ali Ibn Sina As An Example Of The Work "Al-Ishorat Wa-At-Tanbihat" (Zien Journal of Social Sciences and Humanities, 2024)
This article about the concept of "Inoyat" in the philosophical views of Abu Ali ibn Sina and the emphases presented in the comments of these Eastern peripatetic philosophers were analyzed. The concept of “Inoyat” is a term that encompasses the relationship between God, the universe, and man. Abu Ali ibn Sina evaluates the concept of grace as an order of goodness that originates from God. The philosopher focuses on the order of goodness in the world through this term. Farobi evaluates "Inoyat" within the framework of the theory of emanation, good-evil and happiness. The philosopher explains the theory of emanation by divine grace. For the world, which exists by emanation, also partakes of God's existence, and needs the divine will to continue its existence. Therefore emanation shows that grace is permanent. Furthermore, the theory of emanation is the best way to understand the existence of evil. Ibn Rushd considers grace to be a special proof of God's existence. The whole universe was created by God's grace and generosity. The philosopher uses the term continuous creation to express this idea. Therefore, God's grace to the world is endless and continuous. According to the philosopher, man is in harmony with the universe. That this harmony points to God's presence is evidence of grace